Excellence in Breeding Training 2022 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
The International Institute of Tropical Agriculture (IITA) in collaboration with Excellence in Breeding (EiB) organized professional training for IITA crop breeders, National Agricultural Research Scheme (NARS) breeders and EiB members. The training was targeted at increasing the skillset of plant breeders to design breeding schemes.